Green-synthesized magnesium oxide using pomegranate rind extract for antibacterial fabric coating - Umair, Muhammad; Wan Norfazilah Wan, Ismail; Nurul Hidayah, Abu Bakar; Hartina, Mohd Yusop; Kumar, Santhana Krishna; Noreen Farzuhana, Mohd Zulkifli (Malaysian Institute of Chemistry, 2026)
This study presents a sustainable approach for imparting antibacterial and deodorizing properties to textile fabrics using magnesium oxide (MgO) synthesized via a green route. Pomegranate (Punica granatum L.) rind extract (PRE), rich in polyphenolic compounds, was employed as a reducing and stabilizing agent in the biosynthesis of MgO. The synthesized MgO were applied onto cotton, polyester, and blend wool fabrics using a dip-dry coating technique. Optimization experiments identified 4 g of rind powder extracted at 130 °C and a 10 mL extract volume as the most effective formulation. Antibacterial efficacy was assessed against Brevibacterium linens, Cutibacterium acnes, and Staphylococcus epidermidis using the disc diffusion method. All coated fabrics exhibited antimicrobial activity, with blend wool showing the most pronounced inhibition zones. Gas chromatography–mass spectrometry analysis confirmed the absence of volatile organic compounds typically associated with body odour in the coated samples. The study demonstrates that PRE-mediated MgO coatings offer a dual-function textile solution for antibacterial protection and odour suppression, using a green, cost-effective, and scalable method.